2019
DOI: 10.2147/copd.s191946
|View full text |Cite
|
Sign up to set email alerts
|

<p>Inflammation and infections in unreported chronic obstructive pulmonary disease exacerbations</p>

Abstract: Purpose: COPD patients often do not report acute exacerbations to healthcare providers – unreported exacerbations. It is not known whether variances in symptoms, airway obstruction, aetiology and inflammatory responses account for differences in reporting of COPD exacerbations. The aims of the study were to compare symptoms, lung function changes, aetiology and inflammatory markers between exacerbations that were reported to healthcare providers or treated, with those that were unreported and untrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
1
9
1
Order By: Relevance
“…It has been observed in COPD patients, that failure to report exacerbations is related to higher risk of emergency department and hospital admission, greater lung function deterioration, and worse SGRQ scores than treated exacerbations and thus, may result in a poorer prognosis when compared to treated exacerbations [13][14][15][16]. Improved reporting and detection of exacerbations has been achieved in COPD through the use of patient completed diaries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been observed in COPD patients, that failure to report exacerbations is related to higher risk of emergency department and hospital admission, greater lung function deterioration, and worse SGRQ scores than treated exacerbations and thus, may result in a poorer prognosis when compared to treated exacerbations [13][14][15][16]. Improved reporting and detection of exacerbations has been achieved in COPD through the use of patient completed diaries.…”
Section: Discussionmentioning
confidence: 99%
“…The mean score during this "pre-exacerbation" period was 11.3 points (SD 2.7) with a mean change of + 4 points (SD 1.8) (p < 0.0001 by paired t-test). The peak symptom score during exacerbation was a mean of 16.4 (3.1) (range [12][13][14][15][16][17][18][19][20][21][22]. The change from baseline was a mean of 9.1 points (SD 2.5) with a range of 5 to 14.…”
Section: Dynamic Changes In Symptoms Over Time and Detection Of Exacementioning
confidence: 99%
See 1 more Smart Citation
“…Historically, the importance of viral and bacterial infections in precipitating COPD exacerbations has been underestimated [31]. More recently, it was found that bacterial infections, and possibly more importantly, viral infections (detected in 52% of patients with acute exacerbations) are associated with exacerbations and that viral infections can potentially trigger secondary bacterial infections [32][33][34]. Sebastian Johnston suggested that increased airway glucose levels detected in COPD patients, which were further increased during acute exacerbations, may be a mechanism through which rhinoviruses enhance bacterial growth [33].…”
Section: Scientific Year In Review: Respiratory Infectionsmentioning
confidence: 99%
“…Cigarette smoking is the most common cause of COPD that accounts for about 85 to 90% of cases. The other causes for COPD include exposure to environmental smoke, passive smoke, occupational exposure, and genetic predisposition [9][10][11]. The common symptoms of COPD are shortness of breath, cough (with or without expectoration), fever, chest tightness, and hemoptysis [12][13][14].…”
Section: Introductionmentioning
confidence: 99%